SPORTS INJURY AND ILLNESS EPIDEMIOLOGY DURING THE 2018 BRAZILIAN YOUTH SCHOOL GAMES: FUTSAL AND JUDO SURVEILLANCE (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2019)
Epidemiology surveillance is the first step in sports injury prevention. This study investigated the prevalence and pattern of injuries and illnesses during the 2018 Brazilian Youth School Games on futsal and judo competitions (CAAE: 99684718.6.0000.5149). The Brazilian Olympic Committee (COB) provided the daily report of injuries and illnesses for the futsal (n=male: 213; female: 209) and judo (n=male: 370; female: 355) athletes. A total of 44 injuries were reported for futsal and 104 for judo. The incidence of injury per player was 0.11 in futsal and 0.15 in judo. In futsal, 54.5% of injuries were caused by contact with another player, 29.5% were non-contact acute injuries and 6.8% were overuse injuries. In judo, 84.6% of injuries were caused by contact with another player and 12.5% were overuse injuries. The most frequently injured locations in futsal were ankle (18.2%), knee (18.2%) and thigh (13.7%). In judo, face and mouth (39.4%), shoulder/clavicle (16.4%) and elbow (10.6%) were most commonly affected. Sprain (64%) and strain (18.1%) were the most common type of injury in futsal. In judo, cut (48%), contusion (30.8%) and sprain (10.6%) were the most frequent. Eighteen and nine percent of the injuries were classified as severe in futsal and judo, respectively, with subsequent sport absence. Finally, futsal and judo had 9.1% and 8.7% of illness, respectively. These data show the most prevalent type, mechanism and location of injuries in young athletes that may be used to develop prevention strategies for future multi sports event.